Characteristics of "Instafamous" and Digital Fame - Dedkaew, Pattanan; Chanvichai, Kittima (Research Community and Social Development Journal, 2024)
Introduction: Digital fame has been widely recognized and promoted individual identity in business, became popular and followed through content creation, valuable personal identity for understanding the role of visitors on social media. These efforts increase attraction, trust, and credibility within the digital community. Main body: 1) Social Media: Social media platforms are fundamental in allowing human beings to reach a global audience using digital technology to create identity, fame, and global community connections. 2) Instagram: Instagram can support content creation, allowing users to share photos, videos, and engaging stories that resonate with followers. 3) Digital Fame: Digital fame arises from the influence and connects the popularity gained in the online world. 4) Instafamous Individuals: The new term "Instafamous" describes individuals who represent popular interests, items, or trends, are famous, and who have garnered significant followings by using the Instagram platform specifically. Conclusion: Instafamous are characterized by sharing popular photos, videos, and stories primarily limited to the Instagram platform. In contrast, Opinion leaders, are highly credible and accepted by groups with the same shared interests. Moreover, Influencers are associated with products and services and drive followers' purchasing decisions for products and services. In addition, Celebrities are widely recognized and followed by the public and media, operating across multiple platforms without restriction. Benefit, Utilization: 4 important concepts in this about Characteristics of "Instafamous" and Digital Fame which is a body of knowledge based on: “digital media representatives,” “voice with influence,” “Instagram reputation-building,” and “storytelling for reliability and trust in the imagination of readers and viewers.”